2019
DOI: 10.1093/jamia/ocz001
|View full text |Cite
|
Sign up to set email alerts
|

Use of mind maps and iterative decision trees to develop a guideline-based clinical decision support system for routine surgical practice: case study in thyroid nodules

Abstract: Objective The study sought to develop a clinical decision support system (CDSS) for the treatment of thyroid nodules, using a mind map and iterative decision tree (IDT) approach to the integration of clinical practice guidelines (CPGs). Materials and Methods Thyroid nodule CPGs of the American Thyroid Association and Korean Thyroid Association were analyzed by endocrine surgeons (domain experts) and computer scientists. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Nine studies report on the duration of viral shedding as assessed by PCR for SARS-CoV-2 RNA 4 11 20 13 14 15 13 25 40 . The minimum duration of RNA shedding detected by PCR was seven days reported in Bullard, the maximum duration of shedding was 35 days after symptom onset in Qian.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies report on the duration of viral shedding as assessed by PCR for SARS-CoV-2 RNA 4 11 20 13 14 15 13 25 40 . The minimum duration of RNA shedding detected by PCR was seven days reported in Bullard, the maximum duration of shedding was 35 days after symptom onset in Qian.…”
Section: Resultsmentioning
confidence: 99%
“…Different evaluation methods were employed in reviewed articles including qualitative methods [ 30 , 33 , 36 – 38 , 41 , 42 , 46 , 47 ], before-after study [ 14 , 19 , 23 , 27 , 33 , 35 , 38 , 43 , 44 ], the odd ratio [ 15 , 28 , 38 ], usability methods [ 19 21 , 23 , 24 , 26 , 28 , 30 , 37 , 47 ], validation or performance evaluation [ 19 , 20 , 22 , 24 , 27 29 , 39 , 40 , 42 , 43 , 56 ], simulation study [ 47 ], and think-aloud evaluation techniques [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is of interest to us that the tree model can be used to generate easy-to-understand rules to guide the prevention and control of MetS. Currently, DT models have been applied in clinical practice, including disease diagnosis, risk of disease occurrence, regression and prognosis [ 38 – 40 ], health economics evaluation [ 41 ], clinical decision support system (CDSS) [ 42 ], and rational and safe drug use [ 43 ], and DT has shown powerful performance and high accuracy in all these aspects. Although studies have shown that the prediction performance of LR is lower than that of the DT, LR is not prone to overfitting and has good generalization ability [ 44 ].…”
Section: Discussionmentioning
confidence: 99%